2010 Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--16923
|View full text |Cite
|
Sign up to set email alerts
|

Student Voices: Service Learning In Core Engineering Courses

Abstract: Undergraduate engineering students were asked about their views of the principal benefits attributable to service-learning (S-L) dispersed through core required courses through surveys, interviews, and focus groups. As S-L continues to become a significant part of the communityengagement movement in higher education, and as more university professors are encouraged to incorporate S-L activities in their course requirements, it is essential that educators build an understanding of what students gain with S-L an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…12,13 Several programs also report that participation in service-learning positively impacts students' determination to continue in engineering (retention) or was a factor in selecting the program (recruitment). 10,14,15 Specifically, Duffy (2009) found that consistently over 60% of students surveyed from year to year at the University of Massachusetts Lowell indicated that engagement in service-learning helped them stay in engineering; females were significantly more likely to agree with this sentiment. 14 First-year students' belief in the usefulness of engineering has been positively correlated to their plans on choosing a career in engineering.…”
Section: Project-based Service-learning Engineering Designmentioning
confidence: 99%
“…12,13 Several programs also report that participation in service-learning positively impacts students' determination to continue in engineering (retention) or was a factor in selecting the program (recruitment). 10,14,15 Specifically, Duffy (2009) found that consistently over 60% of students surveyed from year to year at the University of Massachusetts Lowell indicated that engagement in service-learning helped them stay in engineering; females were significantly more likely to agree with this sentiment. 14 First-year students' belief in the usefulness of engineering has been positively correlated to their plans on choosing a career in engineering.…”
Section: Project-based Service-learning Engineering Designmentioning
confidence: 99%
“…The goal was to have students exposed to S-L in on average one course in each of eight semesters during their engineering program with an overarching aim to graduate better engineers and more engaged citizens. Previous papers have summarized earlier results [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%